Answer:
see explanation
Step-by-step explanation:
Given
(x - 3) × (x + 4) = 0, that is
(x - 3)(x + 4) = 0
The zero product indicates that (x - 3) = 0 or (x + 4) = 0
x - 3 = 0 ⇒ x = 3
x + 4 = 0 ⇒ x = - 4
Thus if x = 3, then
(3 - 3)(x + 4) = 0 × (x + 4) = 0
Similarly if x = - 4 the output is zero
If p then q. P, therefore q.
Answer:
1 foot and 5 inches.
Step-by-step explanation:
He jumped 6 ft. 9 inch. 6.9+1.5 = 8.4
Hi there!
![\large\boxed{x = 40}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7Bx%20%3D%2040%7D)
We can solve for x knowing that the sum of interior angles in a triangle is 180°.
The square at the bottom indicates a right angle, or 90°. Therefore:
180 = 90 + x + (x + 10)
Combine like terms:
180 = 100 + 2x
Subtract 100 from both sides:
180 - 100 = 2x
80 = 2x
Divide both sides by 2:
x = 40.
Answer:
24cm, 36cm y 48cm
Step-by-step explanation:
Tu necesitas multiplicar cada lado por 4 porque 4 es el factor de escala.
(Lo siento si mi explicacion es mala, no se mucho Español, entonces no puedo explicar muy bien)